Comparative efficacy of commercial ylang-ylang (Cananga odorata) essential oils from India and Thailand against larval Aedes aegypti (L.) (Diptera: Culicidae) - Chaiphongpachara, Tanawat; Laojun, Sedthapong (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study was to determine the comparative larvicidal efficacy of commercial ylang-ylang (Cananga odorata) essential oils from India and Thailand against the Aedes aegypti mosquito to be used as a guideline for Aedes mosquito control. Materials and Methods: The bioassay for the larvicidal activity of commercial ylang-ylang essential oils in this experiment was modified from the World Health Organization standard protocols. The concentration ranges at 0.025, 0.050, 0.075, 0.100, 0.125, and 0.150 ppm in each treatment were used for testing, and four replicates were used per concentration. The larval mortality was observed and recorded 24- and 48-h after exposure. Results: The results of this study clearly revealed that commercial ylang-ylang essential oils from India and Thailand were highly toxic to the larvae of the dengue vector Ae. aegypti, and Indian ylang-ylang had an LC50 value of 0.064 ppm, whereas Thai ylang-ylang had an LC50 value of 0.042 ppm after 24-h exposure. Conclusion: This study revealed the efficacy of commercial Indian and Thai ylang-ylang essential oils as natural vector control for the larval stage of the dengue vector Ae. aegypti. Usually, natural larvicide products are not commonly found in the market due to complex production processes. The results of this research support the use of commercial essential oils to aid in further control of Aedes mosquito larvae populations in the community. J. Adv. Vet. Anim. Res., 7(3): 391-396, Sep 2020 http://doi.org/10.5455/javar.2020.g433